Informal employment or informal firms? Regulatory enforcement and the transformation of the informal sector - Sanjay Jain (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
While there is general agreement that regulatory avoidance is an important part of firms' decisions to produce in the informal sector, there is much less agreement on how regulation and enforcement affect firms' decisions on, inter alia, which sector they locate in, their employment decisions, and whether to transition from one sector to another. In this paper, we focus on this set of questions: how does the regulatory regime affect these sectoral location decisions by firms? In particular, how are these decisions affected in environments where there are regulatory spillovers, so that each firm's decision, on whether to comply with applicable regulations, also carries implications for other firms? We construct a theoretical model that incorporates firms' decisions on their mode of production, encompassing not just the sector and level of production, but also the level of employment, and consider how these might be affected by varying degrees of regulatory spillovers in their operating environment. The main contribution of this research is to provide a clearer understanding of the interplay of regulation and its enforcement on the one hand, and firm decision-making about employment and output on the other, in a modelling environment where these issues are not dealt with in separate black boxes.
Keywords: O17; D04; J46; L51; 330; informal sector; regulatory spillovers; informal employment